A critical study of the laws governing spam in Malaysia / Anas Bashari … [et al.] - Bashari, Anas; Abd Rahman, Ahmad Za'im; Abdul Aleem, Ameerul Shafiq (2014)
This research mainly focuses on the issue of the laws governing spam in Malaysia. This research deals with the issue of the governance and enforcement of laws in curbing the spam in Malaysia. The laws used to govern spam in Malaysia include the Communications and Multimedia Act 1998, the Penal Code, the Evidence Act 1950 and the Personal Data Protection Act 2010. The series of literature are reviewed as we compare the laws in Malaysia with the laws in other countries including United States of America, Australia and Singapore. From the literature review as well as the background of the research, it is evident that the question of proliferations of spam in Malaysia is the issue which has become a national agenda which the rate of spam that was sent had been increasing in a catastrophic rate. The challenges and the problem of the governance and enforcement of laws regarding spam in Malaysia are demonstrated in regulating this research. This study also hopes to improve the current laws that governing spam and also to assist the policy maker in drafting the specific law on spam.